Detection and characterization of beta-adrenergic receptors and adenylate cyclase in coated vesicles isolated from bovine brain - Chuang, DM (J Neurosci, 1986)
To assess whether internalization of beta-adrenergic receptor occurs in the CNS, we have isolated clathrin-coated vesicles from bovine forebrain and examined them for the presence of beta-adrenergic receptor binding and adenylate cyclase activities. A coated vesicle enriched preparation isolated by successive D2O-Ficoll density gradient centrifugations was applied to a glass bead permeation column to achieve further purification. Two major peaks of protein were eluted from the column and monitored by electron microscopy and SDS-PAGE. Peak II contained almost exclusively coated vesicles (98%), whereas peak I, which appeared in the void volume, contained larger smooth vesicles and few coated vesicles. beta-Adrenergic receptor binding to peaks I and II was measured with 125I-cyanopindolol (CYP) as ligand in Sepharose 4B column assays. 125I-CYP was found to bind specifically and saturably to both peaks I and II with a Bmax of 28 +/- 4 and 32 +/- 3 fmol/mg protein, respectively. 3H-CGP 12177, a hydrophilic beta-adrenergic receptor ligand, did not label receptors present in peak II, but it specifically bound to synaptic plasma membranes (SPM) prepared from bovine hippocampus and, to a lesser extent, to peak I. These results suggest that receptors present in coated vesicles are cryptic in nature. In the displacement of 125I-CYP binding by (-)-isoproterenol, addition of 50 microM GppNHp caused a significant “right shift” with SPM and peak I but not the peak II preparation. Adenylate cyclase activities could also be detected in both peaks I and II (specific activities, 21 +/- 0.6 and 24 +/- 0.5 pmol cAMP/mg protein/min, respectively).(ABSTRACT TRUNCATED AT 250 WORDS)